Peluang Pemanfaatan Big Data di Perpustakaan: Sebuah Kajian Literatur - Aliwijaya, Araf (Perpustakaan Universitas Gadjah Mada, 2023)
The accumulation of information created and stored in organizations, including libraries, has led to the emergence of amounts of data known as big data. This research aims to describe opportunities for using big data in libraries. The method used in this research uses a qualitative approach with a literature review method. Data sources were obtained from various literature such as books, scientific articles, websites and others. The big data phenomenon has an influence on libraries in utilizing technology. Data created in libraries should be used to support library policies using data science concepts. Data science is the science used to manage data so that it is useful for libraries. Opportunities for using big data in libraries include collection recommendations, book layout based on user behavior, analysis of knowledge trends, helping with collection development policies, automatic classification and helping with library promotion. The application of big data in libraries can improve the quality of policy making, restructure library services and publications.